2017
DOI: 10.5530/jppcm.2017.4.64
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Rational Medicines Prescribing in Healthcare Facilities in Four Regions of Tanzania

Abstract: Objective: The purpose of the study was to measure rational medicines prescribing in healthcare facilities from selected regions in Tanzania was found to be 18.1% while that containing antibiotics was 67.7% and the average number of medicines per prescription was 2.3. The proportion of medicines prescribed by generic was 95.7%while one that contained medicines in line with the National Essential Medicines List was 96.7%. The overall IRDP for the current study was 3.81with optimal level of 5. Kilimanjaro regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(56 citation statements)
references
References 11 publications
7
36
13
Order By: Relevance
“…The study finding was less than the findings of another study by [10] for African Regions (25%), study in Pakistan (27.1%) [26] and Tanzania 18.1% [27]. It was higher than the research findings of another study in Saudi Arabia of value 2%…”
Section: Discussioncontrasting
confidence: 67%
“…The study finding was less than the findings of another study by [10] for African Regions (25%), study in Pakistan (27.1%) [26] and Tanzania 18.1% [27]. It was higher than the research findings of another study in Saudi Arabia of value 2%…”
Section: Discussioncontrasting
confidence: 67%
“…The finding of this study was less than those found in previous studies (14) (25) (31) (27). However, the percentage was higher compared to that reported at the public health facilities of Tanzania (56.2%) (26). The findings of this study could be an indication that some drugs may have been out of stock.…”
Section: Patient-care Indicatorscontrasting
confidence: 93%
“…The IRDP of these government hospitals in Freetown was lower than that obtained from some other studies. From a study of rational prescribing in Tanzania, the overall IRDP was 3.8 and that of facilities in urban areas like the ones in this study was 3.42 [41]. In Western China, the IRDP was 3.32 ranging from 3.12 to 3.98 across 10 selected provinces [16].…”
Section: Discussionmentioning
confidence: 85%